Pola Komunikasi Organisasi Ketua Tim Sepakbola City Of Heroes Surabaya untuk Mengkoordinasi Anggota dalam Organisasi - Tri Prasetijowati; Fierda Nurany; Muhammad Novi Julia Resa (Public Sphere Review, 2023)
Organizational communication is very important for every organization because communication within an organization is necessary for the team leader to coordinate every member. The pattern of organizational communication is also important for leadership in an organization because, with a good organizational pattern, the team leader can coordinate members effectively and comfortably. In the implementation of the organizational pattern of the city of heroes Surabaya football team leader, the researcher found the communication pattern used by the leader as: a) Wheel Communication Pattern, b) Chain Communication Pattern, c) Y Communication Pattern, and d) Star Communication Pattern. These communication patterns are used by the city of heroes Surabaya football team leader and are considered to be the most effective.